Grounded Immittance Simulation and PID Control Application - Channumsin, Orapin; Unhavanich, Sumalee; Roongmuanpha, Natchanai; Tangsrirat, Worapong (My University, 2026)
This communication introduces a grounded immittance function simulator. The circuit employs a single differential voltage to current converter (DVTC) in association with three passive elements. The grounded series type RL and RC simulator can be realized by selecting the proper position of all passive elements. The equivalent resistance, inductance, and capacitance accomplished from the proposed circuit can be adjusted with a passive resistor. DVTC non-idealities on the proposed simulator are also discussed in detail. The voltage mode PID controller has been suggested as an application using the proposed simulator. The performance of the proposed simulator and controller applications have been carried out through PSPICE simulation. The results are certified by the theoretical prediction.
Keywords: immittance simulator; PID controller; RC simulator; RL simulator